Validity, reliability and reproducibility of three methods used to measure tooth widths for Bolton analyses - Naidu Devan; Scott Justin; Ong Desmond; Ho Christopher T.C (Sciendo, 2023)
Vernier calipers have traditionally been used as the 'gold-standard' for tooth width measurements. New digital methods may prove to be as valid, reliable and reproducible as caliper measurements.